The contemporary garden - Abbs, Barbara; Phaidon Press (London ; New York, NY : Phaidon Press, 2009)
This is an accessible and affordable overview of 100 contemporary gardens from the early 1920s onwards. It features all types of gardens, including conceptual spaces, water and roof gardens, and urban parks.
"First published as The Garden Book 2000"--Colophon.
Includes index.
ARC
Keywords: Gardens -- Design -- History -- 20th century; Gardens -- Pictorial works; Gardens